2020
DOI: 10.1002/wps.20769
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal mental health: a review of progress and challenges

Abstract: Perinatal mental health has become a significant focus of interest in recent years, with investment in new specialist mental health services in some high‐income countries, and inpatient psychiatric mother and baby units in diverse settings. In this paper, we summarize and critically examine the epidemiology and impact of perinatal mental disorders, including emerging evidence of an increase of their prevalence in young pregnant women. Perinatal mental disorders are among the commonest morbidities of pregnancy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
454
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(469 citation statements)
references
References 200 publications
7
454
1
7
Order By: Relevance
“…Safety concerns include not only the sense of safeness regarding medical treatments (e.g., psychotropics) but also structural inequalities and disadvantages that impact women’s well-being (such as insecure employment, domestic violence, poverty, insecure immigrant status, etc. ), all of which are well-known vulnerability factors for the development of emotional disorders in general and in the peripartum period in particular [ 47 ]. The perception of emotional, instrumental, and informational support includes the access and the availability of formal and informal parenting support (both for mothers and fathers); this is closely associated with perceived loneliness and is another protective factor for the development of perinatal depression and stress [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Safety concerns include not only the sense of safeness regarding medical treatments (e.g., psychotropics) but also structural inequalities and disadvantages that impact women’s well-being (such as insecure employment, domestic violence, poverty, insecure immigrant status, etc. ), all of which are well-known vulnerability factors for the development of emotional disorders in general and in the peripartum period in particular [ 47 ]. The perception of emotional, instrumental, and informational support includes the access and the availability of formal and informal parenting support (both for mothers and fathers); this is closely associated with perceived loneliness and is another protective factor for the development of perinatal depression and stress [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ICD‐11 approach was adopted to reflect the diagnostic practices of obstetricians and other health care providers, whose primary clinical focus tends to be on the woman’s pregnancy, childbirth, delivery and postpartum care, and who tend to make diagnoses such as “postpartum depression” and “postpartum psychosis” 92 . For mental health specialists, the psychiatric presentation is of primary importance, and the fact that its onset is during pregnancy or postpartum is more commonly thought of as a course qualifier.…”
Section: Harmonization At the Disorder Levelmentioning
confidence: 99%
“…Perinatal period is a challenging time of substantial emotional, physiological, social, familial, and role changes[ 1 , 2 ]. These changes may affect psychological and physical resources, resulting in increased susceptibility of psychological problems, including depression, anxiety, and stress[ 3 ]. A systematic review observed that depression, anxiety, and stress symptoms co-existed in the perinatal period[ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perinatal mental disorders during pregnancy and postpartum period are associated with considerable maternal, infant, and child morbidity and mortality[ 8 - 10 ]. In addition, they lead to huge economic burden on health and social care[ 3 ]. Therefore, effective intervention is imperative.…”
Section: Introductionmentioning
confidence: 99%